An Updated Systematic Review of Evidence-Based Practices for Management of Rehabilitation Femoral Anteversion and Intoeing Gait in the Pediatric Population - Fiki Ferindra Mulrony; Arkhan Kurniawan (The International Journal of Medical Science and Health Research, 2025)
INTRODUCTION: Intoeing gait secondary to increased femoral anteversion (IFA) is a prevalent pediatric condition and a common source of parental concern. Despite its typically benign, self-resolving nature, management strategies have varied widely, and the evidence base for non-surgical interventions has historically been weak. This systematic review aims to provide an updated analysis of the evidence for rehabilitation management, focusing on functional outcomes rather than solely on the correction of the underlying bony torsion. METHODS: This review was conducted following the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) 2020 guidelines. A comprehensive search of PubMed, Google Scholar, Semanthic Scholar, Springer, Oxford Academic was performed to identify studies published up to October 2024. Studies evaluating non-surgical rehabilitation interventions for intoeing gait associated with IFA in children aged 3-16 years were included. Randomized controlled trials (RCTs) and non-randomized studies of interventions (NRSIs) were appraised using the Cochrane Risk of Bias 2 (RoB 2) and Risk Of Bias In Non-randomized Studies - of Interventions (ROBINS-I) tools, respectively. Data on study design, participants, interventions, and a minimum of 15 distinct outcomes—including femoral anteversion angle (FAA), foot progression angle (FPA), hip rotation range of motion, and functional metrics like tripping frequency—were extracted and synthesized narratively. RESULTS: Seventeen studies, comprising 5 RCTs and 12 NRSIs with a total of 1,215 participants, met the inclusion criteria. The evidence strongly reaffirms that IFA has a high rate of spontaneous resolution, with longitudinal studies demonstrating significant decreases in FAA without active treatment. Interventions such as twister cables and non-specific corrective shoes were found to be ineffective. In contrast, specific orthotic interventions demonstrated functional benefits; gait plates were shown to significantly improve FPA by up to 11.1°, and medial-wedge insoles were effective in reducing the frequency of falls in 80.8% of children. Targeted physical therapy programs, including strengthening of hip external rotators and gait training, resulted in statistically significant improvements in hip external rotation range of motion, FPA, and postural control. DISCUSSION: The synthesized evidence supports a paradigm shift in the management of IFA-associated intoeing, moving away from attempts to alter the natural history of bony development towards a focus on managing functional impairments. For the majority of asymptomatic children, parental education and observation remain the standard of care. For a subset of children with significant functional limitations, such as frequent falls or poor balance, targeted interventions like gait plate orthoses or structured physical therapy can provide meaningful symptomatic relief and functional improvement. The quality of the available evidence is variable, with many studies having a moderate to serious risk of bias, highlighting the need for more rigorous research. CONCLUSION: While the natural history of increased femoral anteversion is overwhelmingly favorable, specific rehabilitation strategies can effectively manage the functional consequences of intoeing gait. There is weak to moderate evidence to support the use of gait plates and targeted physical therapy for symptomatic children. Ineffective historical treatments should be abandoned in favor of an evidence-based, function-focused approach.